The UNESCO-endorsed traditional foodways approach facilitated the launch of a new nationwide initiative in Kenya - Morimoto, Yasuyuki; Maundu, Patrick (2025)
The Indigenous Knowledge intellectual assets Documented and Digitized (IKDoDi) program, as part of Kenya Vision 2030, aims to document Kenya's rich indigenous knowledge including medicine, food, technologies, and cultural heritage as intellectual property. In 2024, the Alliance of Bioversity International and the International Center for Tropical Agriculture (the Alliance)’s established partner, the National Museums of Kenya (NMK), spearheaded the program's first phase by conducting an extensive series of training sessions across 13 of the country’s 47 counties. A total of 780 participants, including key local community members, county and national government officials, and other stakeholders, participated in these sessions.